Cricket protein-based composite film containing Andrographis paniculata leaf extract-based nanoparticles for meat emulsion - Aunzar Bashir Lone; Sunil Kumar; Rana Muhammad Aadil; Abdo Hassoun; Abderrahmane Aït-Kaddour; Zuhaib F. Bhat (Applied Food Research)
A cricket (Acheta domestica) protein (Crik-Prot)-based composite film was developed to preserve the quality of the goat meat emulsion (Got-met-Emul). The A. paniculata leaf extract-based nanoparticles (And-Pan-NPs) were used as an active agent for Crik-Prot-based film. The addition of And-Pan-NPs [0.5 % (T1), 1.0 % (T2) and 1.5 % (T3)] imparted antimicrobial and antioxidant properties to the film [indicated by the results of total phenolic and flavonoid contents, DPPH, ABTS and FRAP activities, antioxidant release (%), and inhibitory halos against S. aureus and Escherichia coli] and significantly (P < 0.05) altered its physicochemical [increased density (g/ml) whereas reduced the WVTR (mg/mt2), transmittance (%) and moisture content (%)] and colour [increased a* and b* and reduced L* values] properties. Crik-Prot-based films incorporated with And-Pan-NPs (0.5–1.5 %) significantly (P < 0.05) enhanced the oxidative stability [protein oxidation (total carbonyl content) and lipid oxidation (TBARS and free fatty acids)], antioxidant potential (ABTS, DPPH, and FRAP activities), and microbiological quality of Got-met-Emul during two weeks storage at 4 ± 1 °C. The Crik-Prot-based film (T1, T2 and T3) enhanced the sensory quality of Got-met-Emul on day 7 of storage and gastrointestinal digestion increased (P < 0.05) the antioxidant potential of Got-met-Emul. The Crik-Prot-based film incorporated with And-Pan-NPs enhanced the storage quality and functional value of Got-met-Emul.